DIGITALIZATION OF RELIGIOUS RITUALS IN BALI'S CULTURAL TOURISM: A STUDY ON LIVE STREAMING OF TRADITIONAL CEREMONIES AND ITS IMPACT ON RELIGIOUS AUTHORITY - Sanjaya, I Gede Wahyu; Agung, I Gusti Ngurah Pertu; Anggara Putu Dharma Putra (UHN IGB Sugriwa Denpasar, 2025)
Digitalization has transformed various aspects of life, including religious practices in the context of cultural tourism in Bali. This research explores the phenomenon of using online media in carrying out traditional Balinese Hindu ceremonial processions, as part of cultural tourism and its impact on religious authorities. Using a qualitative approach, this research analyzes how digitalization enables global access to sacred rituals and how these changes influence the perceptions of local communities, tourists and religious leaders. The findings reveal that the use of technology, especially online media, can increase the visibility of Balinese culture internationally, but also raises challenges related to the commodification of rituals and shifts in religious authority. Apart from that, there is starting to be a debate about the legality of online processions, this needs to be of special concern to policy-making authorities, especially in Hinduism. Several policy proposals were presented in this research. It is hoped that this study will be able to contribute to the discourse on the role of technology in the transformation of religious practices and cultural tourism, which has implications for cultural preservation policies and spirituality-based tourism management.